Perancangan Stasiun Kerja Ergonomis untuk Operator Pemotongan Bahan Baku di Pabrik Genteng Jatiwangi, Kabupaten Majalengka - Dony Susandi; Arif Rijaluddin; Abdul Chaliq (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
In the production department of a manufacturing company, ergonomic, healty and safety should be a majorconcern. It’s a departement with an high accident work rate. One of approach method in the improvement ofworking methods of cutting provider of raw materials are antrhopmometri in ergonomics, its can be used toimprove the working tools of the operator so that work equipment is used in accordance with the standardsbody anthopometri operator. Nordic body map used to recognize the parts of the body operators that havecomplaint at the time of cutting raw material that aim to reduce the complaints that occur when they doinghis job. The study was conducted with the biomechanical approach to the condition before and after work.Previous measurements of anthropometric dimensions of the body to obtain a standard tool used byoperators of production department. Biomechanical analysis focused only on the link and joint body partsoperators has complaints while working to obtain the energy consumption before and after work. The initialdimension of the raw material table slider 350 x 25 cm with a single cutting of the raw material resulting inrepeated cuts. The result of dimensional redesign raw material table slider that indicate significantdifferences, the dimension needed are 530 x 70 cm. By using raw materials slider table current conditionthe energy expenditure result are 4,6375 kcal/min. Based on standard workload Lehman 3,75 kcal/min, theenergy expenditure operators showed that cuts the raw material requires greater energy. Through theredesign of the raw material table slider and better cutting methode, the forces and moments acting on theoperators when work will create the new workload position. The energy expenditure of the new workloadposition indicate better result and operators doing their job with a standard workload.